PENENTUAN HARI – HARI BESAR ISLAM PADA TAHUN 1450 H DENGAN MENGGUNAKAN KEKONGRUENAN ZELLER - Ade Novia Rahma (LPPM Universitas Bina Bangsa, 2021)
Zeller’s congruence system can be used to determine the days of a calendar system. Determination of Islamic holy days can be completed by using the expansion of Zeller’s congruence. The basic theories used in calculating the determination of one day are modulo arithmetic and floor functions. The Hijriyah calendar system is one of the broadest dating systems in Indonesia and other Muslim countries used to determine the commemoration of Islamic holy days. Based on the results of literature studies obtained 10 Islamic days in 1450 Hijriyah